2000
DOI: 10.1046/j.1365-2958.2000.01922.x
|View full text |Cite
|
Sign up to set email alerts
|

The NRAMP proteins of Salmonella typhimurium and Escherichia coli are selective manganese transporters involved in the response to reactive oxygen

Abstract: NRAMPs (natural resistance‐associated macrophage proteins) have been characterized in mammals as divalent transition metal transporters involved in iron metabolism and host resistance to certain pathogens. The mechanism of pathogen resistance is proposed to involve sequestration of Fe2+ and Mn2+, cofactors of both prokaryotic and eukaryotic catalases and superoxide dismutases, not only to protect the macrophage against its own generation of reactive oxygen species, but to deny the cations to the pathogen for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
332
2
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(348 citation statements)
references
References 84 publications
(114 reference statements)
13
332
2
1
Order By: Relevance
“…However, the regulation of manganese importers is slightly at odds with this model: the proton-driven manganese importer MntH is induced (by OxyR) when E. coli is exposed to H 2 O 2 (141), not O 2 − -and the ATP-driven importer MntABC is induced in Stapholococcus aureus under the same circumstances by its PerR system (142). Further, mutations that eliminate these systems sensitize a variety of microbes to H 2 O 2 (143) (141).…”
Section: How Does Manganese Protect Microbes Against Oxidative Stress?mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the regulation of manganese importers is slightly at odds with this model: the proton-driven manganese importer MntH is induced (by OxyR) when E. coli is exposed to H 2 O 2 (141), not O 2 − -and the ATP-driven importer MntABC is induced in Stapholococcus aureus under the same circumstances by its PerR system (142). Further, mutations that eliminate these systems sensitize a variety of microbes to H 2 O 2 (143) (141).…”
Section: How Does Manganese Protect Microbes Against Oxidative Stress?mentioning
confidence: 99%
“…Further, mutations that eliminate these systems sensitize a variety of microbes to H 2 O 2 (143) (141). In explaining these data, some workers have speculated that Mn may scavenge H 2 O 2 as well as O 2 − , since carbonate-bound manganese shows a catalase-like activity in vitro (144).…”
Section: How Does Manganese Protect Microbes Against Oxidative Stress?mentioning
confidence: 99%
“…Nutritional metals, such as manganese, copper, cobalt, and zinc are available as the divalent cation in aerobic environments, and are thus soluble. Whereas cytoplasmic (inner) membrane transporters of free metal ions are well characterized in bacteria (9)(10)(11)(12), translocation across the outer membrane and into the periplasm has not been described. In principle, outer membrane pores with no or low selectivity should readily accommodate the diffusion of these small, soluble nutrients that are needed only in low quantities (4,5).…”
mentioning
confidence: 99%
“…Thus, our finding that divalent metals increase levels of protein in the membrane by 90-120% is significant. Recent studies on prokaryotic Nramp homologues from S. typhimurium and E. coli have shown that transcription of these proteins is diminished when the cells are exposed to divalent transition ions (11,12), presumably caused by promoter elements that recognize divalent metals (12). In our case, we suspect that the metals serve a substrate-protective role, through structural stabilization, which may benefit insertion and͞or shield the protein from proteases.…”
Section: Discussionmentioning
confidence: 59%
“…Recently, the manganese transport functions of bacterial Nramp homologues (MntH) from Escherichia coli, Salmonella typhimurium, and M. tuberculosis have been demonstrated (11)(12)(13). Thus the resistance of the host against the pathogen, and the pathogenicity of the microorganism, may depend on the performance of the individual Nramp or homologous protein.…”
Section: Overexpression Purification and Site-directed Spin Labelinmentioning
confidence: 99%